(3egGLQjf (B/ ## Muhåajiråin /s - (3fOhi, eYjfĎGdqOjf GMeO(B. ## Nadvåi, Mu°åinuddåin.s (b, 1952)
On the lives of the companions of Prophet Muòhammad, d. 632 with special reference to their immigration from Mecca to Medina, Saudi Arab.
Includes bibliographical references.
Keywords: Muòhammad, -- Prophet, -- -632 -- Companions